Conidial heat resistance of various strains of the food spoilage fungus Paecilomyces variotii correlates with mean spore size, spore shape and size distribution. (November 2020) - van den Brule, Tom; Lee, Cheuk Lam Sherlin; Houbraken, Jos; Haas, Pieter-Jan; Wösten, Han; Dijksterhuis, Jan
Graphical abstract: Highlights: Quantification of heterogeneity in spore size, shape and size distribution. Spore size can be equally measured with microscopy and coulter counter. Coulter counter and flow cytometry showed a bimodal spore size distribution. Spores size, shape and size distribution correlate with conidial heat resistance. Abstract: Contamination by spores is often the cause of fungal food spoilage. Some distinct strains of the food spoilage fungus Paecilomyces variotii are able to produce airborne conidia that are more heat-resistant than similar species. These ellipsoid asexual spores can vary in size between strains, but also within strains. Here, we compared four measurement techniques to measure conidia size and distribution of five heat-sensitive and five heat-resistant P. variotii strains. Light microscopy (LM), Scanning Electron Microscopy (SEM) and Coulter Counter (CC) were used to measure and compare the spherical equivalent diameter, while CC and flow cytometry were used to study spore size distributions. The flow cytometry data was useful to study spore size distributions, but only relative spore sizes were obtained. There was no statistic difference between the method used of spore size measurement between LM, SEM and CC, but spore size was significantly different between strains with a 2.4-fold volume difference between the extremes. Various size distribution and shape parameters were correlated with conidial heat resistance. We found significant correlations in mean spore size, aspect ratio, roundness and skewness in relation to heat resistance, which suggests that these parameters are indicative for the conidial heat resistance of a P. variotii strain.